2019
DOI: 10.1186/s12864-019-5651-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression analysis of Trichoderma virens RNA reveals a dynamic transcriptome during colonization of Zea mays roots

Abstract: Background Trichoderma spp. are majorly composed of plant-beneficial symbionts widely used in agriculture as bio-control agents. Studying the mechanisms behind Trichoderma -derived plant benefits has yielded tangible bio-industrial products. To better take advantage of this fungal-plant symbiosis it is necessary to obtain detailed knowledge of which genes Trichoderma utilizes during interaction with its plant host. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 92 publications
1
26
0
Order By: Relevance
“…Overall, the percentage of downregulated genes was higher in both treatment conditions ( Figure 9 ). These results were in alignment with the findings of Liu et al (2014), and Ma et al (2015), who reported that the abundance of downregulated DGEs was significantly higher compared to upregulated genes under PEG stress [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, the percentage of downregulated genes was higher in both treatment conditions ( Figure 9 ). These results were in alignment with the findings of Liu et al (2014), and Ma et al (2015), who reported that the abundance of downregulated DGEs was significantly higher compared to upregulated genes under PEG stress [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…Deep ribonucleic acid (RNA) sequencing studies are achievable for all plant species by exploring transcriptome profiles of model and non-model organisms, under various conditions. These high-throughput sequencing techniques are widely used to create transcriptome data, which enables researchers to identify the differential expression profile of genes in plants under different treatment conditions [17][18][19]. In recent times, transcriptomic approaches have gained much attention for identifying the gene regulatory network associated with drought-stress tolerance in plants [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Before root contact, in the WT strain, genes encoding peroxidases, cellulases, sugar transporters and in general carbohydrate‐related genes are repressed. In full agreement with our results, it was recently described that during the interaction of Trichoderma virens with maize, there is global repression of genes encoding cell‐wall‐degrading enzymes (Malinich et al ., 2019). In our view, these observations suggest that suppression of metabolic processes related to the degradation of complex carbohydrates in the fungus is necessary to establish a beneficial interaction with the plant, likely as a result of the adaptation of the fungus to the availability of simple carbohydrates such as sucrose provided by the roots (Macías‐Rodríguez et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Trichoderma could also alleviate the abiotic and/or biotic stress as plant symbionts through the colonization of plant roots and establishing a communication with the host plant via chemical signals. These signals may induce the plant resistance against stresses by secreting phytohormones (e.g., salsylic acid and jasmonate) and other secondary metabolites (Malinich et al 2019). Then, Trichoderma may support the bio-protection against the phytopathogens by release antibiotic compounds, competing for nutrition and space, improve the plant uptake of water and nutrients, and acidify ambient environment.…”
Section: Trichoderma For Sustainable Agriculturementioning
confidence: 99%